Experimental Models of Type 2 Diabetes Mellitus Induced by Combining Hyperlipidemic Diet (HFD) and Streptozotocin Administration in Rats: An Integrative Review - Ana Karolinne da Silva Brito; Ana Victória da Silva Mendes; Boris Timah Acha; Amanda Suellenn da Silva Santos Oliveira; Joyce Lopes Macedo; Akemi Suzuki Cruzio; Maria das Graças Prianti; Raquel Rodrigues de Abreu; Massimo Lucarini; Alessandra Durazzo; Maria do Carmo de Carvalho e Martins; Daniel Dias Rufino Arcanjo (Biomedicines)
Type 2 diabetes mellitus (DM2) is a metabolic disorder characterized by chronic hyperglycemia associated with low insulin production and/or insulin resistance. A high-fat diet (HFD) combined with a low dose of streptozotocin (STZ) in an animal model produces a disease that mimics type 2 diabetes mellitus in humans. However, there is wide variation in the methods of inducing diabetes in terms of the dose of STZ, the duration of the induction period, and the composition of the diet used, all of which could result in biological responses that are not typical of the disease. This review aims to investigate the characteristics of an experimental model of type 2 diabetes mellitus by combining a high-fat diet with low doses of streptozotocin in Wistar rats. This is an integrative review conducted by searching in the Medline, Lilacs, and Embase databases using the keywords “type 2 diabetes mellitus”, “high-fat diet”, “streptozotocin” and “Wistar rats”. Articles published in English between 2018 and 2025 were included. The induction of DM2 in young male rats with a high-fat HFD for a period of at least 3 weeks followed by a low dose of STZ resulted in metabolic, histological, inflammatory, and oxidative changes, and alterations in the signaling pathways of glycemic and lipid metabolism in different tissues, replicating the characteristics observed in humans. HFD-fed + STZ-induced Wistar rats constitute an effective animal model for studying DM2.